2017
DOI: 10.1111/1440-1681.12759
|View full text |Cite
|
Sign up to set email alerts
|

Compared effects on cerebral oxygenation of ephedrine vs phenylephrine to treat hypotension during carotid endarterectomy

Abstract: While both ephedrine and phenylephrine are currently used to treat hypotension occurring during carotid endarterectomy (CEA) under general anaesthesia, phenylephrine may have deleterious effects on the cerebral watershed, due to its exclusively vasoconstrictive action. In this controlled, double-blind randomised trial, we compared the effects of ephedrine and phenylephrine administered in a standardised algorithm to treat the first hypotensive event occurring since induction of anaesthesia until carotid cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Later, ephedrine can also be used for neuropathic oedema although it is not licensed but indicated in the British National Formularies (BNF). Emerging clinical trials are investigating therapeutic potential in other diseases such as labour pain, vasopressors, and preeclampsia [23][24][25]. Another example is atropine, which in 2001 had licenses with the Medicines and Healthcare products Regulatory Agency (MHRA) for treatment like bradycardia and prevention of cholinergic effects on the heart after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Later, ephedrine can also be used for neuropathic oedema although it is not licensed but indicated in the British National Formularies (BNF). Emerging clinical trials are investigating therapeutic potential in other diseases such as labour pain, vasopressors, and preeclampsia [23][24][25]. Another example is atropine, which in 2001 had licenses with the Medicines and Healthcare products Regulatory Agency (MHRA) for treatment like bradycardia and prevention of cholinergic effects on the heart after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the 9 RCTs [13][14][15][16][17][18][19][20][21] included in the analysis are shown in Table 1. The study by Bassard et al 14 included patients aged between 40 and 90 years, while the rest of the trials included all adult patients older than 18 years.…”
Section: Resultsmentioning
confidence: 99%
“…A similar randomized controlled study to ours found a higher restoration of ipsilateral and contralateral rSO 2 after administration of ephedrine compared to phenylephrine and therefore recommends to prefer ephedrine. However, in our study, no significant difference was found in a decrease in rSO 2 after administration between both vasopressor agents [30].…”
Section: Discussionmentioning
confidence: 65%